2016
DOI: 10.1002/jmor.20592
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic analyses of the high deformability of adhesive toe pads in White's tree frog, Litoria caerulea

Abstract: White's tree frog (Litoria caerulea) has large, adhesive toe pads that are among the softest of all known biological structures. To explore the morphological basis for the physical properties of the toe pads, the internal microstructure of the toe pads in L. caerulea was examined using both light and transmission electron microscopy. Three design elements that are distinct from other areas of skin were observed. First, the keratinocytes comprising the adhesive surface of the toe pad all contained keratin filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Overall, the epidermal morphology found in this study agrees with the extensive description for the same species by Ernst (). The presence of skewed cells in the second most apical layer of epidermal cells in Hyla cinerea (this study), Litoria caerulea (Nakano & Saino, ) and Staurois parvus (Drotlef et al. ) contradicts cell skewing to be a mere age effect, as suggested previously (Schuberg, ; Ernst, ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Overall, the epidermal morphology found in this study agrees with the extensive description for the same species by Ernst (). The presence of skewed cells in the second most apical layer of epidermal cells in Hyla cinerea (this study), Litoria caerulea (Nakano & Saino, ) and Staurois parvus (Drotlef et al. ) contradicts cell skewing to be a mere age effect, as suggested previously (Schuberg, ; Ernst, ).…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the epidermal morphology found in this study agrees with the extensive description for the same species by Ernst (1973a). The presence of skewed cells in the second most apical layer of epidermal cells in Hyla cinerea (this study), Litoria caerulea (Nakano & Saino, 2016) and Staurois parvus (Drotlef et al 2015) contradicts cell skewing to be a mere age effect, as suggested previously (Schuberg, 1891;Ernst, 1973a). We hypothesise that the longitudinally skewed tonofibrils increase the stiffness of the apical epidermis during the transmission of shear loads deeper into the digital pad, possibly increasing friction by the distribution of mechanical stresses over a larger volume of pad material (Xue et al 2017) and maintaining the structural integrity of the epidermal surface.…”
Section: Transmission Of Shear Loadssupporting
confidence: 90%
See 3 more Smart Citations